2005
DOI: 10.1002/ceat.200407145
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanisms of Photocatalyzed Total Oxidation Reaction of Hydrocarbon Species with Titanium Dioxide in the Gas Phase

Abstract: Starting with the main characteristics of the photocatalyst titanium dioxide, a catalytic cycle passed during the total oxidation of alkanes and alkenes is proposed where the oxygen vacancies are actually the active sites at which the redistribution of electrons is easily possible. These sites are formed by the electron-hole pairs generated by the adsorption of UV light. Based on the presented mechanism, a rate equation is derived, taking into account the main influences on the photocatalyzed reactions in ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
(30 reference statements)
1
9
0
Order By: Relevance
“…3f ). It was found that increasing the gas flow rate from 25 to 65 ml min −1 caused the ratio of methane oxidation to decrease linearly from almost 100 to ∼76%, which is consistent with the fact that the photocatalytic reaction is a rate-determined process 35 .…”
Section: Resultssupporting
confidence: 72%
“…3f ). It was found that increasing the gas flow rate from 25 to 65 ml min −1 caused the ratio of methane oxidation to decrease linearly from almost 100 to ∼76%, which is consistent with the fact that the photocatalytic reaction is a rate-determined process 35 .…”
Section: Resultssupporting
confidence: 72%
“…This chapter reviews the complete oxidation of trace levels of GHG methane present in the atmosphere into CO 2 and H 2 O according to the reaction scheme: CH 4 + 2O 2 → 2H 2 O+ CO 2 . [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40,41], [42], [43], [44], [45], [46], [47], [48], [49], [50], [51,52] Table 3 summarizes some research on the photocatalytic oxidation of methane and/or other low molecular weight alkanes under UV.…”
Section: Photocatalytic Oxidation Of Methanementioning
confidence: 99%
“…Although some authors like Kaliaguine [30] used a vanadium derivative (V 5+ /SiO 2 ) as well as TiO 2 , very often authors used TiO 2 based photocatalysts, [36][37][38][39][41][42][43] and investigated the kinetics of the total oxidation of methane, ethane, ethene and propene using TiO 2 . Others like Krishna [40] Wataru [45] studied the photocatalytic decomposition of chlorodifluoromethane, methane and tetrachloromethane over TiO 2 because these compounds have the same structure but different constituents.…”
Section: Insert Tablementioning
confidence: 99%
“…In particular, photocatalytic oxidation has shown to be a suitable solution for air treatment [3,4]. However, limited research has been devoted to the photocatalytic oxidation of propane [5][6][7][8]. In a recent review, Finger et al, discuss the kinetics and mechanism of the photocatalytic oxidation of alkanes and alkenes with TiO 2 photocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review, Finger et al, discuss the kinetics and mechanism of the photocatalytic oxidation of alkanes and alkenes with TiO 2 photocatalysts. They indicate that a large electron supply is not sufficient to facilitate a fast propane oxidation, but electrons in appropriate oxygen defect sites seem to be much more important for the catalytic cycle to work [ 6 ]. They propose a mechanism in which irradiation is able to produce oxygen vacancies.…”
Section: Introductionmentioning
confidence: 99%